Pattern and trends of Helicobacter pylori genotypes in gastric cancer: A Kenyan 8-year study - Njenga, Priscilla; Njau, Allan; Moloo, Zahir; Revathi, Gunturu; Tshibangu, Evariste; Yamaoka, Yoshio (Frontiers in Medicine, 2023)
Background Notable geographic and temporal variations in the prevalence and genotypes of H. pylori, in relation to gastric pathologies, have been observed; however, their significance and trends in African populations is scarcely described. The aim of this study, was to investigate the association of H. pylori and its respective CagA and VacA genotypes with gastric adenocarcinoma, and to describe the trends of H. pylori genotypes over an 8-year period (2012-2019). Materials and Methods A total of 286 samples of gastric cancer cases and benign controls (one-to-one matching), from three main cities in Kenya, between 2012 and 2019 were included. Histologic evaluation, and CagA and VacA genotyping using PCR, was performed. Distribution of H. pylori genotypes was presented in proportions. To determine association, a univariate analysis was conducted using a Wilcoxon rank sum test for continuous variables, and a Chi squared test or Fishers Exact test for categorical data. Results The VacA s1m1 genotype was associated with gastric adenocarcinoma, (OR=2.68 [confidence interval of 95%: 0.83-8.65]; p=0.108), whilst VacA s2m2 was associated with a reduced probability of gastric adenocarcinoma (OR=0.23 [CI 95%: 0.07-0.78]; p=0.031). No association between CagA and gastric adenocarcinoma was observed. Conclusion Over the study period, an increase in all genotypes of H. pylori was seen, and although no predominant genotype was noted, there was significant year-to-year variation, with VacA s1 and VacA s2 showing the greatest variation. VacA s1m1 and VacA s2m2 were associated with increased, and reduced risk of gastric cancer respectively. Intestinal metaplasia and atrophic gastritis did not appear to be significant in this population.